Analisis Butir Soal UAS Biologi 2018/2019 Kelas X dan XI SMAN 11 Kota Bengkulu - Deka Putriani; Fadila Turahmah; Nefi Ratna Sunarti; Pisi Ismarliana; Ahmad Walid (Journal of Biology Learning, 2020)
About UAS subjects biology made by the teacher SMAN 11 of Bengkulu before never analyzed either quality and quantity. The purpose of this study is to analyze about UAS biology at the school year 2018/2019 in the base  with a taxonomy of bloom and the lurch. In this research using the descriptive with a quantitative form of research and qualitative. The collection of technique used is data a interview. The instruments are used is the sheet about UAS biology and inquiries interview teachers biology. The result can be seen  from the lurch about UAS made by the teacher carried out in SMAN 11 of Bengkulu is the category of being by 60% and the distinguishing about be categorized enough and both have the proportion  of the devision of the same of 36%, the results of the devision of the distribution of the difficulty of based on a taxonomy of bloom not meet criteria, due to the problem is more classified as in the category of C1 and C2 of 40%.Keywords : analysis about,  taxonomy of bloom, UAS